How Sustainability Ratings Might Deter ‘Greenwashing’: A Closer Look at Ethical Corporate Communication - Parguel, Béatrice; Benoît-Moreau, Florence; Larceneux, Fabrice (2011)
Of the many ethical corporate marketing practices, many firms use corporate social responsibility (CSR) communication to enhance their corporate image. Yet, consumers, overwhelmed by these more or less well-founded CSR claims, often have trouble identifying truly responsible firms. This confusion encourages ‘greenwashing’ and may make CSR initiatives less effective. On the basis of attribution theory, this study investigates the role of independent sustainability ratings on consumers’ responses to companies’ CSR communication. Experimental results indicate the negative effect of a poor sustainability rating for corporate brand evaluations in the case of CSR communication, because consumers infer less intrinsic motives by the brand. Sustainability ratings thus could act to deter ‘greenwashing’ and encourage virtuous firms to persevere in their CSR practices.
Keywords: Sustainability ratings; Attribution Theory; CSR communication; Ethical corporate marketing